2021
DOI: 10.1177/10781552211046574
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of outpatient high-dose cytarabine and intermediate-dose cytarabine for consolidation therapy in acute myeloid leukemia

Abstract: Introduction The standard of care consolidation therapy for acute myeloid leukemia is high-dose cytarabine or intermediate-dose cytarabine, which are traditionally given inpatient. At Moffitt Cancer Center, we have moved the administration of high-dose cytarabine and intermediate-dose cytarabine to the outpatient setting through the inpatient/outpatient program. To facilitate outpatient administration, high-dose cytarabine and intermediate-dose cytarabine are given in a shorter interval of every 10 h instead o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…One of the biggest limitations of administrating outpatient cytarabine is ensuring accessibility to and funding for daily oncology clinics operating long enough to provide q12h cytarabine. Potential solutions to this include shortening the dosing interval to q10h from q12h 26 . Our institution has moved to outpatient administration of cytarabine consolidation on a q24h interval in attempt to reduce hospitalization days, prolonged clinic hours associated with q12h dosing, and improve patient quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest limitations of administrating outpatient cytarabine is ensuring accessibility to and funding for daily oncology clinics operating long enough to provide q12h cytarabine. Potential solutions to this include shortening the dosing interval to q10h from q12h 26 . Our institution has moved to outpatient administration of cytarabine consolidation on a q24h interval in attempt to reduce hospitalization days, prolonged clinic hours associated with q12h dosing, and improve patient quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Potential solutions to this include shortening the dosing interval to q10h from q12h. 26 Our institution has moved to outpatient administration of cytarabine consolidation on a q24h interval in attempt to reduce hospitalization days, prolonged clinic hours associated with q12h dosing, and improve patient quality of life. Although our study does not directly analyse cost benefits, its clinical results are in line with those of other studies that did.…”
Section: Analysis Of Outpatient Cytarabine Was Done Based On Inpatientmentioning
confidence: 99%
“…Twelve publications were categorised as retrospective data studies that reported analyses of existing health service data; characteristics of which are detailed among the data papers in Table 3. Articles published between 2008 and 2021 with one outlier from 1982, they predominately focus on demonstrating the feasibility, safety, clinical outcomes and efciencies associated with the AC pathway within difering international settings [2,3,[30][31][32][33][34][35][37][38][39]. Patient-reported outcomes were not included as a part of these analyses.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Here, an additional 1443 adult cancer treatment episodes were successfully delivered via AC across the 6-year period (2005-2011), avoiding treatment delays, maximising treatment outcomes and freeing up hospital beds for acutely unwell patients [3]. Within other international literature, transitioning chemotherapy regimens that were traditionally given as an inpatient to an outpatient basis to manage increasing demand on inpatient beds was also described by Li and colleagues [30] as a key driver. Within non USA literature, avoiding delays in treatment due to limited bed capacity was described by Bakhshi, Singh, and Swaroop [2] as one of the drivers for piloting the ambulatory model to give consolidation chemotherapy to paediatric haematology patients in India.…”
Section: Cancer Services In Generalmentioning
confidence: 99%